Relational Consciousness as Eco-Spiritual Formation: Interreligious Construction with Rosemary R. Ruether and Neo-Confucianism - Joo Hyung Lee (Religions)
This study investigates the theological and philosophical interplay between Rosemary Radford Ruether’s ecofeminist theology and Neo-Confucian cosmology in the context of Korean Protestant Christianity. By exploring intolerant interpretations of the Christian creation story, it critiques the anthropocentric domination of nature and proposes a reformed ecological spirituality. The research integrates Ruether’s covenantal and sacramental traditions, arguing for the significance of “relational consciousness” as a framework for eco-spiritual formation. Drawing from Ruether’s examination of creation myths and Neo-Confucian perspectives, this study asserts the necessity in reshaping Christian theology to embrace human interdependence with nature and the cosmos. It proposes that Korean Christians, influenced by Calvinist theology, must move beyond human dominion over nature to a role of co-creator and nurturer of the ecosystem, advocating for an eco-theological renewal that centers on relational consciousness for spiritual formation.